A new Zn mixed‐ligand coordination polymer fiber for solid‐phase microextraction of the anticancer drug tamoxifen. Issue 11 (15th November 2018) - Jafari, Mostafa; Amani, Vahid
Abstract: A new metal‐organic coordination polymer, [Zn(μ‐mptrz)(mptrz)(μ‐en)0.5 ]n (mptrz − is 4‐methyl‐1, 2, 4‐triazole‐3‐thiolato), has been used to prepare a solid‐phase microextraction fiber using the direct immersion method. The fiber was well characterized, and showed superior properties. Scanning electron microscopy of the fiber shows a very porous and homogenous coating. The thermal stability, adhersivity and chemical stability were excellent for extracting analytes from harsh media and desorbing them in a high thermal inlet of a gas chromatograph. An anti‐cancer drug, tamoxifen, was extracted with this fiber and then analyzed by using gas chromatography with flame ionization detection. The main factors affecting the extraction of tamoxifen were optimized. The detection limit and linear range were 0.62 and 4–800 μg L −1, respectively. The intra‐day and inter‐day relative standard deviations were obtained at different concentrations, using a single fiber, and found to be 14.1–15.4 and 13.3%, respectively. The results were then compared with other works. Tamoxifen in two urine samples was successfully analyzed with the proposed method.